THE IMPACT OF HYDRAULIC STRUCTURES ON ECOLOGICAL BALANCE AND ASSESSMENT METHODS (American Journal of Pedagogical and Educational Research, 2025)
This article delivers an in-depth scientific analysis of the impact of hydraulic structures—including dams, weirs, canals, and reservoirs—on ecological balance, offering a critical synthesis of contemporary international research, regional practice, and the development of robust assessment methods. It traces the evolution of hydraulic engineering from its roots in human civilization to its central role in modern water management and environmental modification, with a particular focus on the dualistic nature of hydraulic infrastructure as both a driver of socio-economic progress and a source of ecological disturbance. The review highlights the mechanisms by which hydraulic structures alter riverine and terrestrial ecosystems, from hydrological and sedimentological regime changes to the fragmentation of habitats, disruption of biological connectivity, and shifts in ecosystem services. It further analyzes the emergence and application of environmental impact assessment (EIA), strategic environmental assessment (SEA), life cycle analysis (LCA), ecohydrological modeling, and biodiversity indicators as tools for quantifying and mitigating these impacts. By presenting global case studies and original examples from Central Asia, the article identifies best practices, persistent challenges, and innovative approaches—emphasizing the critical need for integrated, adaptive, and participatory frameworks in balancing engineering goals with environmental stewardship. The article concludes with practical recommendations for advancing the science and governance of hydraulic infrastructure to support sustainable development and ecological resilience.